Pengaruh Waktu Tinggal Hidrolik Terhadap Alkalinitas, Asam Volatil Dan pH Dalam Pengolahan Sludge Instalasi Pengolahan Air Limbah (IPAL) Pulp Dan Kertas Menggunakan Bioreaktor Hibrid Anaerobik - Yasmarli, Yasmarli; Ahmad, Adrianto; HS, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pulp and paper industries growth significantly especially in Indonesia that in their operations generate potential waste to contaminate the environment. Type of waste that generated by pulp and paper industries mostly liquid that could be processed in wastewater treatment installation (WWTI). WWTI still generate amount volume of sludge waste, so it need to be in special handling. One of the alternative that can be reduce volume of sludge waste is anaerobic hybrid bioreactor. This technology use suspended and settle microorganism that integrated in bioreactor system. This research aim to determine the influence of hydraulic retention time (HRT) toward alkalinity, volatile acid and pH in processing of sludge waste from pulp and paper wastewater treatment installation using anaerobic hybrid bioreactor. This research start from seeding time that 100 ml/day sludge waste added to 1 Litre of cows’s feces extract for 10 days. Next stage is acclimatisation with throw and put methode and continued with start up where sludge waste flewed in to bioreactor with 5 days HRT. Last stage is variate HRT for 4 days; 3 days and 2 days. Result of this experiment show that average optimum pH operations is 6,6. Alkalinity 2010 mg/L otherwise volatile acid concentration is 43 mg/L. Bioreactor have high stability with value 0,026 in optimum 4 days HRT.Keyword:Alkalinity, Anaerobic, Bioreactor, Hybrid, Hydraulic Retention Time, Paper, pH, Pulp, Volatile Acid, Wastewater